Existence of serotonin and neuropeptides-immunoreactive endocrine cells in the small and large intestines of the mole-rats (Spalax leucodon) - Yaman, M.; Bayrakdar, A.; Tarakci, B. G. (Churchill Livingstone, 2012)
The present study was conducted to clarify the regional distribution and relative frequency of endocrine cells secreting serotonin, substance P (SP), cholecystokinin-8 (CCK-8), vasoactive intestinal polypeptide (VIP) and neurotensin in the small and large intestine of the mole-rats (Spalax leucodon), by specific immunohistochemical methods. In the small and large intestine of mole-rats (Spalax leucodon), serotonin, SP and VIP were identified with various frequencies, but CCK-8 and neurotensin were not observed. Most of the IR cells in the small and large intestine were located in the intestinal crypt and epithelium however, they were more frequency in the intestinal crypt. Serotonin-IR cells were detected throughout the whole intestinal tract, predominantly in the duodenum and colon. SP-IR cells were demonstrated throughout the whole intestinal tract except for the ileum and rectum with highest frequencies in the cecum. VIP-IR cells were found in all parts of the small intestine except for the large intestine. In conclusion, the general distribution patterns and relative frequency of intestinal endocrine cells of the mole-rats (Spalax leucodon) was similar to those of some rodent species. However, some species-dependent unique distributions and frequencies characteristics of endocrine cells were also observed in the present study. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Endocrine cell; Immunohistochemistry; Intestine; Neuropeptides; Mole-rat